2016
DOI: 10.3390/nu8050245
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Proanthocyanidins from Sea Buckthorn (Hippophae Rhamnoides L.) Seed against Visible Light-Induced Retinal Degeneration in Vivo

Abstract: Dietary proanthocyanidins (PACs) as health-protective agents have become an important area of human nutrition research because of their potent bioactivities. We investigated the retinoprotective effects of PACs from sea buckthorn (Hippophae rhamnoides L.) seed against visible light-induced retinal degeneration in vivo. Pigmented rabbits were orally administered sea buckthorn seed PACs (50 and 100 mg/kg/day) for 14 consecutive days of pre-illumination and seven consecutive days of post-illumination. Retinal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“… 45 revealed a marvellous depletion in MDA concentration and higher antioxidant defense level in animals with the supplementation of H. rhamnoides extract. H. rhamnoides extract provides protection from oxidative stress due to its higher antioxidative activity with its ability to scavenge free radicals 46 and its ability to reduce the activation of caspase-3, downregulating the expression of pro-apoptotic genes Bax, and upregulating the expression of anti-apoptotic genes Bcl-2 47 . Better growth performance in broilers in this study could also be connected with potent antioxidative properties of the H. rhamnoides extracts.…”
Section: Discussionmentioning
confidence: 99%
“… 45 revealed a marvellous depletion in MDA concentration and higher antioxidant defense level in animals with the supplementation of H. rhamnoides extract. H. rhamnoides extract provides protection from oxidative stress due to its higher antioxidative activity with its ability to scavenge free radicals 46 and its ability to reduce the activation of caspase-3, downregulating the expression of pro-apoptotic genes Bax, and upregulating the expression of anti-apoptotic genes Bcl-2 47 . Better growth performance in broilers in this study could also be connected with potent antioxidative properties of the H. rhamnoides extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Berries of SBT have been used in the Chinese, Mongolian, and Tibetan traditional medicine for the treatment of various diseases for more than 1,000 years [13]. Many researchers have paid much attention to SBT for its various medicinal values, such as anti-inflammatory and immunoregulatory effects [14,15,16]. All parts of SBT are rich sources of bioactive agents [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PF was effective using a lower dose than those experiments. It is reported that proanthocyanidins from the seed of sea backthorn protect against light damage in the retina [ 19 ]. In the study, rabbits were administered proanthocyanidins (50 mg/kg and 100 mg/kg BW) for three weeks.…”
Section: Discussionmentioning
confidence: 99%